Pengembangan Pengetahuan Masyarakat Desa Kawunglarang Menyiapkan Jahe Sebagai Bahan Jamu - Waluyo, Endrian; Kurniasih, Nia; Ramadhani, Susan Sintia; Ismail, Rian; Ramdhan, Jhidan (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Dependence on chemical drugs is a problem in the modern era, so innovation is needed. But besides innovation, it can also be done against the narrative of past medicine, one of which is herbal medicine. So the empowerment of herbal medicine as a substitute for modern medicine needs to be raised again as a characteristic of Nusantara culture. So, modern society needs to re-examine how to prepare medicinal plants to be suitable for consumption and provide the right effectiveness. Knowledge is needed to process and prepare the right ginger plants as herbal medicine ingredients. Objective: Increase community knowledge in cultivating land and proper fertilization for ginger plants as herbal medicine ingredients. Method: Community service is carried out through direct practice in the field and the use of regional languages ​​followed by female farmers in Kawunglarang Village, Rancah, Ciamis, West Java. Result: Community knowledge has increased from previously having an average of 80.5 to 99. Conclusion: Increased knowledge is expected to be one of the indicators for preserving the cultivation of red ginger as one of the typical Indonesian medicinal plants